How to Value Orphan Drugs? A Review of European Value Assessment Frameworks - Blonda, Alessandra; Denier, Yvonne; Huys, Isabelle; Simoens, Steven (Frontiers in Pharmacology, 2021)
Background: Decision-makers have implemented a variety of value assessment frameworks (VAFs) for orphan drugs in European jurisdictions, which has contributed to variations in access for rare disease patients. This review provides an overview of the strengths and limitations of VAFs for the reimbursement of orphan drugs in Europe, and may serve as a guide for decision-makers. Methods: A narrative literature review was conducted using the databases Pubmed, Scopus and Web of Science. Only publications in English were included. Publications known to the authors were added, as well as conference or research papers, or information published on the website of reimbursement and health technology assessment (HTA) agencies. Additionally, publications were included through snowballing or focused searches. Results: Although a VAF that applies a standard economic evaluation treats both orphan drugs and non-orphan drugs equally, its focus on cost-effectiveness discards the impact of disease rarity on data uncertainty, which influences an accurate estimation of an orphan drug’s health benefit in terms of quality-adjusted life-years (QALYs). A VAF that weighs QALYs or applies a variable incremental cost-effectiveness (ICER) threshold, allows the inclusion of value factors beyond the QALY, although their methodologies are flawed. Multi-criteria decision analysis (MCDA) incorporates a flexible set of value factors and involves multiple stakeholders’ perspectives. Nevertheless, its successful implementation relies on decision-makers’ openness towards transparency and a pragmatic approach, while allowing the flexibility for continuous improvement. Conclusion: The frameworks listed above each have multiple strengths and weaknesses. We advocate that decision-makers apply the concept of accountability for reasonableness (A4R) to justify their choice for a specific VAF for orphan drugs and to strive for maximum transparency concerning the decision-making process. Also, in order to manage uncertainty and feasibility of funding, decision-makers may consider using managed-entry agreements rather than implementing a separate VAF for orphan drugs.